Melt-memory of polyethylenes with halogen substitution: Random vs. precise placement. (2nd April 2019) - Marxsen, Stephanie F.; Alamo, Rufina G.
Abstract: Polyethylenes with Br, Cl, or F atoms placed at an equal distance of 21 or 15 backbone carbons are known to crystallize as homopolymers, accommodating the halogen in layered crystallites. In contrast, analogs with a random distribution display a crystallization path dominated by sequence-length selection. A consequence of the sequence selection of random copolymers is a constrained interlamellar region and broader melting peaks displaced at higher temperatures than analog systems with the precise placement. Precision and random ethylene-vinyl halides are excellent models to substantiate as a general behavior the strong melt-memory observed in random ethylene 1-alkene copolymers, which contrasts with a much weaker or lack of melt-memory seen in linear polyethylene. While precision polyethylenes with Br, Cl, or F placed on each 21st or 15th backbone carbon show negligible deviation in crystallization rate above the observed melting, the increase in crystallization rate of analogs with the random distribution is observed even from melts 60° above the observed melting point. These data give further evidence of the sharp difference of melt-memory behavior between homopolymers and random copolymers, regardless of whether the co-unit participates in the crystalline regions. Differences in melt-annealing behavior, and a recrystallization of precision polyethylenes that depends on the polymorph that melts prior a subsequent cooling, are also highlighted. Graphical abstract: Image 1 Highlights: Model precision and random ethylene-vinyl halides generalize the strong melt-memory observed in random copolymers. Random halogen polyethylenes show enhanced crystallization rate from melts 60° above observed melting. Precision halogen polyethylenes show negligible change in crystallization rate above observed melting. Crystallization rate is insignificantly altered by annealing heterogeneous random copolymers melts for up to 1000 min. Recrystallization of precision halogen polyethylenes depends on polymorph that melts prior to crystallization.